Hazelnut allergome overview and Cor a gRNAs identification - Ciro Gianmaria Amoroso; Giuseppe Andolfo (BMC Plant Biology)
Abstract Background Corylus species (hazelnuts) are a valuable source of nutrients and are widely consumed worldwide. Nevertheless, Corylus avellana (Cor a) contains 13 allergens (Cor a 1, Cor a 2, Cor a 6, Cor a 8, Cor a 9, Cor a 10, Cor a 11, Cor a 12, Cor a 13, Cor a 14, Cor a 15, Cor a 16, and Cor a TLP) that have been deposited into the official database (WHO/IUIS) for allergen nomenclature. The recent availability of several Corylus genomes provided opportunities to explore allergome variability, and thus to develop hypoallergenic varieties using modern biotech approaches. Certainly, the identification of CRISPR-Cas9 guide RNA (gRNA) is a pivotal step in achieving this goal. User-friendly web tools include limited reference genomes to design CRISPR-Cas9 gRNAs, while bioinformatic software for custom analysis require advanced command-line skills. Results This work explored the evolutionary trajectories of allergenic Cor a homologs in C. avellana, C. americana, C. heterophylla, and C. mandshurica genome assemblies. 52 Cor a orthologs were found in the analyzed species, and a recent tandem duplication of Cor a 1 was found in C. americana. Three new gene models were predicted in C. avellana and C. mandshurica for Cor a 16 and Cor a 10. Additionally, we identified 56 Cor a isoallergens, of which ten Cor a isoforms. Furthermore, phylogenetic analysis sheds light on the evolutionary dynamics of three hazelnut allergens revealing the evolutionary complexity of Cor a 1, Cor a 2, and Cor a TLP within the Corylus genus. A list of multiple gRNAs designed for the CRISPR-Cas9 system was provided for the singular and multiple silencing of Cor a homologs in each Corylus genome. Conclusions This study enhances our knowledge on the evolutionary path of Cor a allergens among Corylus species and provides highly accurate on-target guides targeting hazelnut allergome.